Increased gulf stream warm core ring formations contributes to an observed increase in salinity maximum intrusions on the Northeast Shelf - Adrienne Silver; Avijit Gangopadhyay; Glen Gawarkiewicz; Paula Fratantoni; Jenifer Clark (Scientific Reports, 2023)
Abstract We present observational evidence of a significant increase in Salinity Maximum intrusions in the Northeast US Shelf waters in the years following 2000. This increase is subsequent to and influenced by a previously observed regime-shift in the annual formation rate for Gulf Stream Warm Core Rings, which are relatively more saline than the shelf waters. Specifically, mid-depth salinity maximum intrusions, a cross-shelf exchange process, has shown a quadrupling in frequency on the shelf after the year 2000. This increase in intrusion frequency can be linked to a similar increase in Warm Core Ring occupancy footprint along the offshore edge of the shelf-break which has greatly increased the abundance of warm salty water within the Slope Sea. The increased ring occupancy footprint along the shelf follows from the near doubling in annual Warm Core Ring formation rate from the Gulf Stream. The increased occurrence of intrusions is likely driven by a combination of a larger number of rings in the slope sea and the northward shift in the GS position which may lead to more interactions between rings and the shelf topography. These results have significant implications for interpreting temporal changes in the shelf ecosystem from the standpoint of both larval recruitment as well as habitability for various important commercial species.